Development and Assessment of Learners’ Experiences with a Virtual Reality Learning Platform: Constructivist and Experiential Learning Pedagogies in Master of Physical Therapy Curriculum - Lovo, Stacey; Leidl, Don; Usunier, Kendra; Paslawski, Teresa; Wesolowski, Mike; Puri, Arjun; Caron, Valerie; Kim, Soo (Imagining SoTL, 2024)
Teaching competencies for psychomotor skill development for manual handling techniques in the cervical regions is necessary for safe practice in physiotherapy. However, grasping anatomy and palpation can be challenging for students, and practice in the lab can lead to discomfort for students. To facilitate teaching and learning of this complex skill, we worked in partnership with a virtual reality (VR) industry partner who developed a customized VR application focusing on transverse ligament stress testing for manual therapy skills for Master of Physical Therapy (MPT) students. In this scholarship of teaching and learning (SoTL) project, eight MPT students participated in the evaluation of an innovative VR learning experience for manual therapy in the cervical spine. Students’ learning experiences with the custom virtual reality learning application were assessed using an observational study design with semi-structured interviews. Interview questions aligned with constructs that are recommended to assess learners’ attitudes toward VR environments. Student participants appreciated the usefulness of the application for studying and practicing the transverse ligament stress test and provided recommendations for enhancing the learning experience.